Isostructural molecular strings linked via conserved dipolar (ether) O center dot center dot center dot C=O short contacts in conformational polymorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2009)
Conformational dimorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoformate and its orthoacetate analogue were characterized using single crystal X-ray diffraction, thermal analysis and hot-stage microscopy techniques. In these polymorphs, the tosyl group adopted different conformations due to the rotation about the O-S bond. A significant variation in the torsion angle for the tosyl group (similar to 56 degrees) was observed for Form II crystal of the orthoformate derivative, which exhibited an intramolecular dipolar S=O center dot center dot center dot C=O (sulfonyl-carbonyl) short contact. An interesting feature in all conformational polymorphs is the formation of an isostructural string (despite the differences in the orientation of the tosyl group) linked via dipolar (ether) O center dot center dot center dot C=O contacts, which is further stitched by other weak interactions to form different layers in their crystal lattice.